The female crucifix : images of St. Wilgefortis since the Middle Ages - Friesen, Ilse E. (Wilfrid Laurier University Press, 2001)
Featuring more than twenty illustrations, including several works of art that were rediscovered by the author and are published here for the first time, The Female Crucifix: Images of St. Wilgefortis Since the Middle Ages provides a new perspective on a very old phenomenon. The legendary bearded female St. Wilgefortis, also known by a variety of other names including "Kummernis" and "Uncumber," was the object of fervent veneration in areas of Western and Central Europe for almost half a millennium. Beginning in the fifteenth century, the legend of her dramatic transformation from a beauti.